Age dynamics of predatory fish infection with nematodes Eustrongylides excisus in Dnipro-Bug estuary and delta of Dnipro - Гончаров, С. Л. (Scientific Progress & Innovations, 2017)
The dependence of infection with nematodes Eustrongylides excisus, Jägerskiöld, 1909 on the age of the predatory fish, such as pike-perch – Sander lucioperca (Linnaeus, 1758), European Perch – Perca fluvial (Linnaeus, 1758) and pike – Esox lucius (Linnaeus, 1758) that were caught in the waters of Dnipro-Bug estuary on the delta of Dnipro was studied. It was shown that with increasing age of the fish prevalence of infection and abundance were also rising. The most affected were fish from older age groups – from 7+–8+ to 9+.